EL TABERNÁCULO DE SANTA CLARA LA REAL DE MURCIA: PROCESO DE RESTAURACIÓN Y HALLAZGO DE LA FIRMA DEL RETABLISTA GANGA - Santiago Godos, Victoria (Imafronte, 1993)
The tabernacle of the Royal Church of Santa Clara, in Murcia, is a very singular specimen of baroque art. In past times it suffered quite important alterations, which led to a recent restoration. The long lasting and laborious work carried out by the author of this paper hod the main goal of returning the physical entirety of the piece. Disappearedparts were carved a new, and a great number of fissures and holes were refilled. Afrer cleaning, the parts damaged or replaced were gilded using sheets of fine gold and traditional techniques. During this process, it was discovered the artist’s signature and the date of 1755 (at an upper part of the work), which ,fitlly confirm the authorship by the reredos maker José Ganga.